Yeni Türk Şiirinde biçim arayışları : Servet-i Fünûn‘dan İkinci Yeni‘ye kadar (1896-1950) - Altun, Sezin Seda (My University, 2019)
Edebi eseri var eden iki temel yapı -içerik (öz/ muhteva) ve biçim (form)- arasındaki ilişki akademik literatürün daimî tartışma konularından biri olmuş, ancak Türk şiiri üzerine yapılan incelemelerde tematik araştırmaların çoğunlukta olduğu görülmüştür. Bu nedenle özellikle şiir incelemelerinde, şiiri kuran iç ve dış yapıyı anlamak onun sunduğu anlamlar ve çağrışımlar dünyasını sezmeyi de kolaylaştıracak; bu da şairin biçimsel arayışlarını hem kendi şiir evreni hem de yaşadığı dönem içinde kavrayabilmek imkânını vereceğinden daha nitelikli sonuçlara ulaşmayı sağlayacaktır.

Although the relation between content and form, the two basic structures that constitute the literary work has been a perennial topic for academic scholarship, in the case of Turkish poetry research has been mainly conducted along thematic lines. Therefore, especially in studies of poetry, an appreciation of the internal and external structures that make up poetry helps to understand the world of meaning and connotation; which will in turn provide better results by letting the reader to comprehend poet's quest for form both in her/ his own poetical universe and through the historical era s/ he is living.
Keywords: Form; Form in Poetry; Formal Change; History and criticism; Nazım Biçimi; Poetic Forms; Şekil Değişiklikleri; Şiirde Biçim; Tarih ve eleştiri; Turkish literature; Turkish poetry; Türk edebiyatı; Türk şiiri